PENERAPAN ALGORITMA MAUT (MULTY_ATTRIBUTE UTILITY THEORY) DALAM PEMILIHAN PUPUK TERBAIK PADA TANAMAN KELAPA SAWIT - Annisa Khairani; Heru Satria Tambunan; M. Fauzan (STMIK Budi Darma, 2019)
Fertilizer is an ingredient that contains one or more nutrients or nutrients for plants to support the growth and development of plants. Oil palm plantations produce large profits so that many forests and old plantations are converted into oil palm plantations. To produce the best palm oil production, it is recommended that fertilizers have the quality and quantity precisely and quickly so that the target in the development of oil palm can be achieved maximally in its growth process. Many methods can be used to solve problems in the scientific field, one of the methods SPK. Researchers used the MAUT (Multy-Attribute Utility Theory) method in solving the problem of selecting the best fertilizer on oil palm plants based on several criteria that were set. Visual Basic 2010 application is the software used in this study. It is hoped that this research can recommend the best fertilizer used on plantations to maintain the quality of oil palm plants.Keywords : SPK, MAUT, Visual Basic 2010, MADM, Microsoft Access